The Effect Of Health Promotion Interventions Through Comic-Based Photonovella Media In Increasing Knowledge And Attitudes About The Dangers Of Smoking Among Middle School Students In Jambi City - Ary Irfan; Solihin Sayuti; Puspita Sari; Adila Solida (International Journal of Medicine and Health, 2024)
Smoking has very negative health consequences. The dangers of smoking must be recognized from school age. The snakes and ladders game is an interesting type of educational media that can be used to increase students' knowledge about the dangers of smoking. The aim of this research is to find out how the use of the snakes and ladders game impacts junior high school students' knowledge about the dangers of smoking.This research is considered quasi-experimental with a non-randomized control group pretest and posttest approach. The number of respondents in this study was 90 students, where respondents were divided into 2 groups, namely the treatment group who were given health education using comic-based Photonovella media and the comparison group using conventional methods (posters). Data were collected using a questionnaire and analyzed using the Wilcoxon Test and Mann Whitney U Test. The results of the Wilcoxon test showed a significant increase in the post test scores for the knowledge and behavior variables in both the treatment and comparison groups, but there was no significant increase in the post test scores for the attitude variables. Then the results of the Mann Whitney U Test (sig.2-tailed) on knowledge (0.007 < 0.05), attitudes (0.217 > 0.05), and behavior (0.024 < 0.05). This indicates that there is a significant difference between the scores of the treatment group and the comparison group on the knowledge and behavior variables, but there is no significant difference on the attitude variable.Comic-based photonovella can be used in the learning process because they are very effective in increasing children's knowledge, attitudes and behavior about the dangers of smoking. Therefore, this can be used as an alternative learning media to increase students' knowledge of health by increasing their knowledge about health.